ANALISIS PENGGUNAAN APLIKASI SISTEM AKUNTANSI PERSEDIAAN (ASAP) TERHADAP EFEKTIVITAS PELAPORAN PERSEDIAAN PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN MUSI BANYUASIN - Ahmad Irfansyah (Institut Rahmaniyah Sekayu, 2022)
This research is used to answer two main problems, namely how to use the Inventory Accounting System Application (ASAP) on the effectiveness of inventory reporting at the Regional Financial and Asset Management Agency of Musi Banyuasin Regency and what efforts should be made to increase the effectiveness of using the Inventory Accounting System Application (ASAP)The results of this study indicate that the financial report reporting of the Inventory Information System Application (ASAP) has been used effectively considering the final results of the inventory obtained are itemized and, however, if viewed from the point of view of using the application in inputting, it can be said to be less effective because inputting errors often occur data where the available menu does not match the data inputted so it is necessary to make adjustments in the input and efforts made by the local government through the Regional Financial and Asset Management Agency of Musi Banyuasin Regency, namely intrinsically and exterinsically in the form of operator assistance, routine checks / checks, application updates. as well as ASAP operator outreach / training.